Hubungan Faktor Risiko Penyakit Jantung Koroner dengan Kejadian Henti Jantung - Ghosalim, Aurell H.; Jim, Edmond L.; Joseph, Victor F. F. (Universitas Sam Ratulangi, 2024)
Abstract: One of the causes of death from cardiovascular disease is cardiac arrest. The most common cause of cardiac arrest is coronary heart disease (CHD). This study aimed to determine the relationship between CHD risk factors and cardiac arrest events at Prof. Dr. R. D. Kandou Hospital. This was an analytical and descriptive study with a retrospective cross-sectional approach. Samples were all patients with cardiac arrest at Gedung CVBC RSUP Prof. Dr. R. D. Kandou from August to November 2023 who had complete medical recors. The sampling technique used total sampling and research instruments using medical record data. The results obtained 37 patients as samples consisting of male (64.9%) and female (35.1%) patients. The chi-square test showed a significant relationship between sex variable and the incidence of cardiac arrest (p=0.011). There was no significant relationship (p>0.05) between the variables of age, family history, hypertension, hyperlipidemia, diabetes mellitus, obesity and smoking with the incidence of cardiac arrest. In conclusion, gender has a significant relationship with the incidence of cardiac arrest. Meanwhile, age, family history, hypertension, hyperlipidemia, diabetes mellitus, obesity and smoking were not significantly related to the incidence of cardiac arrest. Keywords: coronary heart disease risk factors; cardiac arrest Abstrak: Salah satu penyebab kematian akibat penyakit jantung ialah henti jantung. Penyebab tersering terjadinya henti jantung dikarenakan oleh penyakit jantung koroner (PJK). Penelitian ini bertujuan untuk mengetahui hubungan antara faktor risiko PJK terhadap kejadian henti jantung di RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ini ialah deskriptif analitik dengan desain potong lintang retrospektif. Sampel penelitian ialah semua pasien henti jantung di Gedung CVBC RSUP Prof. Dr. R. D. Kandou pada bulan Agustus sampai November 2023 dengan data rekam medik lengkap. Teknik pengambilan sampel menggunakan total sampling dan instrumen penelitian menggunakan data rekam medik. Hasil penelitian mendapatkan 37 pasien sebagai sampel penelitian terdiri dari pasien berjenis kelamin laki-laki (64,9%) dan perempuan (35,1%). Hasil uji chi-square memperoleh hubungan bermakna antara variabel jenis kelamin terhadap kejadian henti jentung (p=0,011). Tidak terdapat hubungan bermakna (nilai p>0,05) antara variabel usia, riwayat keluarga, hipertensi, hiperlipidemia, diabetes melitus, obesitas, dan merokok terhadap kejadian henti jantung. Simpulan penelitian ini ialah jenis kelamin memiliki hubungan bermakna dengan kejadian henti jantung. Pada faktor usia, riwayat keluarga, hipertensi, hiperlipidemia, diabetes melitus, obesitas dan merokok tidak didapatkan hubungan bermakna dengan kejadian henti jantung di RSUP Prof. Dr. R. D. Kandou. Kata kunci: faktor risiko penyakit jantung koroner; henti jantung